Obstructive Sleep Apnea in Adults: The Role of Upper Airway and Facial Skeletal Surgery. Issue 4 (October 2016) - Garg, Ravi K.; Afifi, Ahmed M.; Sanchez, Ruston; King, Timothy W.
Abstract : Summary: Obstructive sleep apnea represents a large burden of disease to the general population and may compromise patient quality of life; workplace and automotive safety; and metabolic, cardiovascular, and neurocognitive health. The disease is characterized by repetitive cycles of upper airway collapse resulting from a lack of pharyngeal airway structural support and loss of muscle tone among upper airway dilators. Polysomnography serves as the gold standard for diagnosis of obstructive sleep apnea and the apnea-hypopnea index is the most commonly used metric for quantifying disease severity. Conservative treatments include lifestyle modification, continuous positive airway pressure treatment, and dental appliance therapy. Surgical treatment options include pharyngeal and facial skeletal surgery. Maxillomandibular advancement has been shown to be the most effective surgical approach for multilevel expansion of the upper airway and may significantly reduce an obstructive sleep apnea patient's apnea-hypopnea index. Patient age, obesity, and the degree of maxillary advancement may be key factors contributing to treatment success.